The Influence of Organizational Culture on Employee Performance in PT. Gas Sembilan Semangat - Rifdah Novia Ramadhani (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The aim of this research is to analyze the impact of organizational culture on employee performance. Knowing & analyzing whether organizational culture has an effect on employee performance. The research method used is a qualitative research method. The population in this study were all employees of PT. Gas Sembilan Semangat employs a total of 20 employees. The number of samples used in this study amounted to 4 employees using intentional capture techniques, namely capture techniques using certain criteria. The data used in this study is the main data, namely by conducting interviews using informants. The data analysis technique used in this research is a qualitative data analysis technique using the discourse analysis method. The results show that employees have several reasons. For example, employees who are not contract employees have reasons because of inadequate working hours, while employees who are contract employees think that it is a form of their rights to become contract employees. Therefore, employees must have a greater commitment to carrying out their work responsibilities.